Analisis filogenetik genus mus berdasarkan gen cytochrome b (cytb) menggunakan metode maximum likelihood - Ma'la, Zilvia Inayatul; Husaini, Nofal Aldi (Maliki Interdisciplinary Journal, 2026)
Phylogenetic analysis is essential to understand evolutionary divergence and relatedness among species within the genus Mus. This study aimed to examine the phylogenetic relationships of 15 Mus species based on cytochrome b (Cytb) using the Maximum Likelihood (ML) method, with Rattus norvegicus as an outgroup. DNA sequences were retrieved from GenBank and analyzed in MEGA 12. The resulting tree revealed major clades separating Eurasian and African lineages. Mus musculus, M. spicilegus, M. macedonicus, and M. cypriacus formed a well-supported clade with short evolutionary distances, indicating close relationships. Asian species such as M. caroli and M. saxicola formed a distinct branch with greater genetic divergence. African species, including M. minutoides, M. musculoides, M. mattheyi, M. indutus, and M. haussa, clustered into a separate lineage that diverged substantially from the Eurasian group. The varying branch lengths captured by ML reflect heterogeneous substitution rates among sites.